Screening and brief intervention for alcohol and other drug use in primary care: associations between organizational climate and practice - Cruvinel, Erica (BioMed Central, 2013)
BACKGROUND: Numerous studies have demonstrated that positive organizational climates contribute to better work performance. Screening and brief intervention (SBI) for alcohol, tobacco, and other drug use has the potential to reach a broad population of hazardous drug users but has not yet been widely adopted in Brazil’s health care system. We surveyed 149 primary health care professionals in 30 clinics in Brazil who were trained to conduct SBI among their patients. We prospectively measured how often they delivered SBI to evaluate the association between organizational climate and adoption/performance of SBI. METHODS: Organizational climate was measured by the 2009 Organizational Climate Scale for Health Organizations, a scale validated in Brazil that assesses leadership, professional development, team spirit, relationship with the community, safety, strategy, and remuneration. Performance of SBI was measured prospectively by weekly assessments during the three months following training. We also assessed self-reported SBI and self-efficacy for performing SBI at three months post-training. We used inferential statistics to depict and test for the significance of associations. RESULTS: Teams with better organizational climates implemented SBI more frequently. Organizational climate factors most closely associated with SBI implementation included professional development and relationship with the community. The dimensions of leadership and remuneration were also significantly associated with SBI. CONCLUSIONS: Organizational climate may influence implementation of SBI and ultimately may affect the ability of organizations to identify and address drug use.